Pharmacokinetics and Pharmacodynamics in Breast Cancer Animal Models - Wang, Wei; Nag, Subhasree; Zhang, Ruiwen (Methods in molecular biology (Clifton, N.J.), 2016)
The study of pharmacokinetics (PK) and pharmacodynamics (PD) in cancer drug discovery and development is often paired and described in reciprocal terms, where PK is the analysis of the change in drug concentration with time and PD is the analysis of the biological effects of the drug at various concentrations over different time courses. While PK is defined by how a compound is absorbed, distributed, metabolized, and eliminated, PD refers to the measure of a compound's ability to interact with its intended target, leading to a biologic effect. Recent advances in anti-breast cancer drug discovery have resulted in several new drugs, but there is still a high attrition rate during clinical development. One reason for this failure is attributed to inappropriate correlation between the PK and PD parameters and subsequent extrapolation to human subjects. In this chapter, we describe the protocols of PK and PD studies in breast cancer models to assess the efficacy of an anti-breast cancer compound, noting the types and endpoints employed, and explain why it is important to link PK and PD in order to establish and evaluate dose/concentration-response relationships and subsequently describe and predict the effect-time courses for a given drug dose.